2010
DOI: 10.1136/bmj.c5729
|View full text |Cite
|
Sign up to set email alerts
|

Effect on peer review of telling reviewers that their signed reviews might be posted on the web: randomised controlled trial

Abstract: Objectives To see whether telling peer reviewers that their signed reviews of original research papers might be posted on the BMJ's website would affect the quality of their reviews. Design Randomised controlled trial. Setting A large international general medical journal based in the United Kingdom. Participants 541 authors, 471 peer reviewers, 12 editors. Intervention Consecutive eligible papers were randomised either to have the reviewer's signed report made available on the BMJ's website alongside the publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 14 publications
3
98
0
1
Order By: Relevance
“…Opponents counter this by arguing that signing will lead to poorer reviews, as reviewers temper their true opinions to avoid causing offence. To date, studies have failed to show any great effect in either direction ( McNutt et al , 1990; van Rooyen et al , 1999; van Rooyen et al , 2010). However, since these studies derive from only one disciplinary area (medicine), the results cannot taken as representative and hence further research is undoubtedly required.…”
Section: Discussion: the Traits Of Open Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Opponents counter this by arguing that signing will lead to poorer reviews, as reviewers temper their true opinions to avoid causing offence. To date, studies have failed to show any great effect in either direction ( McNutt et al , 1990; van Rooyen et al , 1999; van Rooyen et al , 2010). However, since these studies derive from only one disciplinary area (medicine), the results cannot taken as representative and hence further research is undoubtedly required.…”
Section: Discussion: the Traits Of Open Peer Reviewmentioning
confidence: 99%
“…Van Rooyen and her colleagues found that open reports correlate with higher refusal rates amongst potential reviewers, as well as an increase in time taken to write review but no concomitant effect on review quality ( van Rooyen et al , 2010). Nicholson and Alperin’s small survey, however, found generally positive attitudes: “researchers … believe that open review would generally improve reviews, and that peer reviews should count for career advancement” ( Nicholson & Alperin, 2016).…”
Section: Discussion: the Traits Of Open Peer Reviewmentioning
confidence: 99%
“…According to its detractors, open review may thus result in worse reports compared 137 to blind review, but this has not been observed in randomized, controlled trials [10,11,27]. 138…”
Section: Pros and Cons Of Open Pre-publication Peer Review 116mentioning
confidence: 99%
“…The most prevalent theme was ethics [1,4,7,8,10,11,18,20,25,26,28,30,31,33,[40][41][42]46]. This theme occurred in 18 (49%) of the articles reviewed.…”
Section: Prevalence Of Themesmentioning
confidence: 99%
“…Fabricating results is ethical misconduct, but authors must also understand that altering data to misrepresent [11,20,31]. Another prevalent theme in the literature was the discussion of different versions of peer review, which was discussed in 12 (32%) of the articles reviewed [2,10,13,19,23,28,29,39,41,44,46,47]. These different methods of peer review include the single-blinded system, doubleblinded system, open system, peer agreement system, and author suggestion-based system ( Table 2).…”
Section: Prevalence Of Themesmentioning
confidence: 99%